Types of Onomatopoeia Found in Comic Jojo's Bizarre Adventure: Jojolion - Ida Ayu Mela Tustiawati; Miarta, I Made Agus Leo (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2023)
This study showed that onomatopoeia is a sound word that describes an event that occurs frequently in daily life. Finding the different types of onomatopoeia used in a comic is the goal of this study. The comic book Jojo's Bizarre Adventure: Jojolion served as the study's data source. This study also uses Elizabeth's (2013) onomatopoeia theory to help identify the many types of onomatopoeia in the Jojo's Bizarre Adventure: Jojolion comic. This study combined the method of observation with a qualitative descriptive approach. Reading comics, identifying and attempting to understand onomatopoeia words and their types, then taking notes on the findings are some of the steps of the observation method that is utilized. This study employed the comic book Jojo's Bizarre Adventure: Jojolion and discovered several types of onomatopoeia, including Mechanical, Fast Motion, Food Preparation and Eating, Fighting, and the last Animal. 50 data of onomatopoeia found in the comic Jojo's Bizarre Adventure: Jojolion, the type of Fast Motion found the most with 31 data or 62%, followed by Fighting with 8 data or 16%, then Mechanical 6 data or 12%, Food Preparation and Eating with 4 data or 8% and Animal 1 data or 2%.